The effect of geniste on Aβ25–35-induced PC12 cell apoptosis through the JNK-dependent Fas pathway. Issue 11 (31st October 2016) - Zheng, Yaojie; You, Fuling; Li, Qiao; Chen, Jingrong; Yang, Hong
Abstract : The β-amyloid protein (Aβ) is considered to be the key factor for inducing Alzheimer's disease (AD). Abstract : The β-amyloid protein (Aβ) is considered to be the key factor for inducing Alzheimer's disease (AD). In recent years, the neuroprotective effects of genistein have drawn increasing attention. However, the molecular mechanisms of GEN (genistein) against Aβ are unclear. In the present study, we investigated the inhibitory effects of GEN on Aβ25–35-induced apoptosis in cultured PC12 cells and the related signaling pathway. Our data show that GEN significantly inhibited Aβ25–35-induced apoptosis of PC12 cells. GEN suppressed Aβ25–35-induced JNK activation and the JNK-dependent upregulation of Fas/FasL at the mRNA and protein levels induced by Aβ25–35 were significantly decreased by GEN. Additionally, GEN inhibited mRNA expression and activity of caspase-3 and caspase-8 induced by Aβ25–35. Together, these findings showed that Aβ-induced apoptosis of PC12 cells proceeds through the Fas/FasL pathway. The JNK signaling plays a critical role in regulating the anti-apoptotic effects of genistein. Thus, our results suggest that genistein can inhibit Aβ-induced apoptosis of PC12 cells through blockage of the JNK activation and subsequent suppression of the JNK-dependent Fas/FasL pathway.